Assessing Impacts of Coal Reform in Shanxi Province on Surrounding Provinces Using Multi-Regional CGE Model - Yalong Han; Toshihiko Masui (Chemical Engineering Transactions)
As the largest coal-producing and exporting region in China, the structural reform of the coal industry in Shanxi Province has profound impacts on the regional economy and environment. Aiming to assess the economic, social, and environmental impacts of coal sector reform, especially the thermal power phasing out in Shanxi Province on its surrounding provinces, including Beijing, Tianjin, Hebei, Shandong, and Jiangsu province, this study constructs a static multi-regional computable general equilibrium model, based on the multi-regional input-output table of 31 provinces, aggregated into three regions: Shanxi Province, surrounding provinces, and other provinces. Under scenarios of reference and thermal power phasing-out policies, the interregional socio-economic activities are simulated. The results reveal that thermal power phasing-out in Shanxi province will significantly promote the carbon neutrality of Shanxi province. It will reduce about 43.49 % carbon emissions of Shanxi province compared to reference scenario, although it will have a negative carbon reduction impact on surrounding area and other provinces. For economy, due to the capital input increasing, thermal phasing-out will have a benefit on GDP growth for each region. However, it will affect the labor mobility among local sectors, especially the labor in power sector will reduce 8.3 % in Shanxi province, while surrounding area and other provinces will have 0.636 % and 0.116 % labor loss in local power sector.